Pengambilan Keputusan Dalam Penerimaan Karyawan Bank Dengan Pendekatan Terstruktur Berbasis Sistem Pakar - N. Tri Suswanto Saptadi; Vini Silviani Sebukita (Jurnal Informatika, 2012)
Development of the information services in recruitment bank employees cannot be supported the availability of the information system component. Meeting the need of the availability of good and competence employees needs to key attention to the recruitment and placement of the employees effectively. The use of expert system in recruitment helps the decision making contribute to the placement of the employees. This effort greatly assists personnel managers in making decisions in a way to minimize the positioning error and to know the characteristics of prospective employees of the bank. The research method begins by collecting facts through interviews and questionnaires. Stages followed by analysis of the problem to get answers. To connect the user to use an expert systems with a system modeling. Development in the addition of applied knowledge through system programming. Application of the system to help managers in making decisions on personnel recruitment. Keywords: recruitment, expert systems and decision making